2017
DOI: 10.12775/jpm.2017.006
|View full text |Cite
|
Sign up to set email alerts
|

Forming the Awareness of Employees in the Field of Information Security

Abstract: Research purpose: The aim of this study is to present the essence and importance of information security awareness in the organisation and to analyse selected methods used in forming employee awareness in terms of information security. Methodology/ approach:This paper is based on literature studies and available reports. Findings:The presented paper suggests that in order to create a positive change in the organisation, information security training should focus on the attitude and behavior of employees. Conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…The rapid development and transformation of information technologies and its use has resulted in a rise in security issues and breaches across the globe (Chmura, 2017). In the Global Information Security Survey conducted by Ernst &Young (EY), it was consistently found that the biggest security vulnerability is lack of awareness by employees (end-users) (EY, 2017).…”
Section: Global Perspective Of Information Security In the Workplacementioning
confidence: 99%
“…The rapid development and transformation of information technologies and its use has resulted in a rise in security issues and breaches across the globe (Chmura, 2017). In the Global Information Security Survey conducted by Ernst &Young (EY), it was consistently found that the biggest security vulnerability is lack of awareness by employees (end-users) (EY, 2017).…”
Section: Global Perspective Of Information Security In the Workplacementioning
confidence: 99%